Relationship of factors in determination of work fatigue in bengkalis district health service employees in the time of covid-19 pandemic - Danil Sahputra; Endang Purnawati Rahayu; Mitra; Oktavia Dewi; Herniwanti (Institute of Computer Science (IOCS), 2022)
Work fatigue is part of the common problems that are often encountered in the workforce, especially work fatigue during the Covid 19 period for employees of the Bengkalis District Health Office. The purpose of this study was to analyze internal factors related to work fatigue during the Covid 19 Period for Bengkalis District Health Office Employees in 2021. This study used an analytical quantitative research type with a Cross-Sectional Analytical design. The research respondents were employees of the Bengkalis District Health Office. All workers with a total of 113 people. This study uses a logistic regression test. The study was carried out from September to October 2021. It showed that the description of work fatigue in the Bengkalis District Health Office was 78 people (69%). These results are based on age P value 0.010 OR 3.370, gender P value 0.924 OR 1.160, working period P value 0.001 OR 4.140, body mass index P value 0.040 OR 2.534, marital status P value 0.029 OR 2.679, duration of work P value 0.142 OR 2,002. Age, years of service, Body Mass Index (BMI), and marital status affect work fatigue in Bengkalis District Health Office employees. It is recommended that the Bengkalis District Health Office implement WFH (Work From Home) during the Covid 19 period, limiting the working period of employees who work 3 years